Decoding the Italian Wine Market: A Quantitative Macro-Economic Examination of Price and Expert Rating Influences - Seth M. Porter (Wine Business Journal, 2024)
This quantitative analysis explores the key determinants affecting the price per bottle and expert ratings within the Italian wine market. It posits that collective reputation, as signified by Geographic Indicators (GIs), Protected Designation of Origin (PDOs), and certification, primarily drive these factors. The study presents a comprehensive contextual backdrop and literature review to address this hypothesis. This conceptual overview is followed by a novel research design, incorporating significant elements influencing wine pricing and expert evaluations. The investigation employs dual multivariate regression models, thereby corroborating and enriching existing literature on the impact of collective reputation in the wine industry. Key findings reveal that PDO ratings and specific certifications such as classico, reserva, millesimato, or organic production significantly influence Italian wines' price and expert ratings. The analysis further quantifies these impacts, suggesting that specific certifications can predict notable increases in wine prices and expert evaluations, underlining the importance of geographic origin and diverse certifications in shaping the market dynamics of the Italian wine industry.